Prognostic Performance of Hestia Criteria in Acute Pulmonary Embolism: A Systematic Review and Meta-Analysis - Yubin Wang MM; Yinhe Feng MD; Rao Du MD; Xiaoya Yang MM; Jifeng Huang MM; Hui Mao MD (Clinical and Applied Thrombosis/Hemostasis, 2022)
Previous studies have suggested that Hestia criteria could effectively identifying patients with acute pulmonary embolism (PE) who were at low risk of mortality for outpatient treatment or early discharge. But the performance of Hestia criteria in stratifying patients at different risk class is still unknown. We sought to comprehensively evaluate the prognostic impact of Hestia criteria for PE. The literatures search was conducted in PubMed, Web of Science and EMBASE from 1 August 2011 to 31 October 2021. Finally, Eight studies with 4110 patients were included in our meta-analysis. Overall, the pool percentage of patients classified as low-risk group and high-risk group were 41.4%% and 58.6% respectively, and the all-course mortality rates of each group were 2.3% and 10.6%, respectively. The pooled rate of PE-related composite adverse outcomes in high-risk group was increasingly higher than in low-risk group (15.7% vs 4.4%). High risk group was also markedly associated with overall mortality (OR: 7.21, 95%CI: 4.96-10.46, p < 0.00001), and PE-related adverse outcomes (OR:5.38, 95% CI:3.95-7.32, p < 0.00001). The pooled sensitivity, specificity, PLR, NLR of Hestia criteria for overall mortality were 0.90 (95% CI:0.83-0.94), 0.43 (95% CI:0.31-0.55), 1.6 (95% CI:1.3-1.9), 0.23 (95% CI: 0.15-0.35), respectively. The area under SROC curve (AUC) was 0.81 (95% CI: 0.77-0.84). The result of our meta-analysis indicate that Hestia criteria can effectively identify PE patients at low risk of poor prognosis with high sensitivity and NPV, but its prognostic role in patients with higher risk class still need to be verified.